Ties that bind - Margolin, Phillip (Margolin, Phillip. Amanda Jaffe novel., 2003)
Lawyer Amanda Jaffe uncovers the trail of a fiercely secret fraternity of powerful and dangerous men behind a political conspiracy A series of seemingly unrelated deaths culminate in the gruesome murder of a U.S. Senator just days before he is going to be his Party<U+2019>s nominee for the Presidency. Portland hometown hero Tim Kerrigan<U+2015>Heisman trophy winner and now District Attorney<U+2015>prosecutes the case. Representing the alleged murderer is Amanda Jaffe, still recovering from the traumatic events that concluded the sensational New York Times bestseller Wild Justice. Her client claims to have information linking the Senator to a mysterious circle of high-ranking judges, public officials, and South American drug lords<U+2015>an affiliation that is rumored to go back 30 years<U+2015>known as the Courthouse Athletic Club. Amanda must hope her client can stay alive long enough for the truth to be revealed.